Simulating reduction of in-flight particles of magnetite concentrate by carbon monoxide. (26th November 2017) - Abolpour, B.; Afsahi, M. M.; Soltani Goharrizi, A.; Azizkarimi, M.
Abstract : In the present study, the reduction of in-flight particles of iron ore concentrate by carbon monoxide has been investigated. A mathematical model was developed for simulating the motion of particles in a CO–Ar gaseous mixture within the reactor. Pre-designed experiments were carried out in a fabricated experimental set-up for validating the model. Excellent agreement between the model predictions and the experimental data approved the accuracy of the model. The nucleation and growth model and the fminsearch optimising method were used for investigating the reaction kinetics. The following equation was obtained relevant to CO reduction of the magnetite concentrate particles: